Do countries with more business-friendly environments receive more aid? - HAN, Ahreum (KDI School, 2015)
This study verifies whether the current aid allocation practice gives a priority to the business environment of aid receiving nations. Since traditional aid practice has registered many unsuccessful results over the last couple of decades, author believe that strengthening the private sector with aid in developing countries is one of good attempts to lift those countries from poverty. Econometric estimations with panel data of 120 developing countries from 2007 to 2012 indicate that the recent aid practice has not much changed from the past practice. Donors respond mainly to the recipients’ economic and physical needs, represented by income level, infant mortality and population, rather than considering the aid’s value for money. In addition, the finding regarding government effectiveness is inconsistent with the existing claim that aid should be allocated more to countries with sound policies and institutions. This paper suggests that donor states carefully consider the soundness of business polices of a recipient country as a prime determinant when selecting where to give aid. Furthermore, donor countries should deliberately design how to utilize their aid resources to strengthen the business policies and regulations for recipient countries.
Thesis(Master) --KDI School:Master of Development Policy,2015